ANALISIS PERUBAHAN TUTUPAN LAHAN PADA KOTA PADANG MENGGUNAKAN CITRA SATELIT - Antika Fardilla; Rifta Septiavi; Ratna Juwita T; Risqi Mutia Arba; Rizka Sefmaliza; Ahmad Rizaldy Fanbudy; Taufiq Afdhal; Aadrean Aadrean; Wilson Novarino (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Land use change is an important issue for urban and regional planners and policy makers, but it is also very useful in conservation planning, food security, and hydrological modeling. Data, information and analysis tools become obstacles in detecting changes in land use. With increasing access to data and current technology, it is hoped that land use observations can be carried out in a simple way but have more accurate results. This study aimed to analyze land cover changes in Padang City 2018-2022, using Landsat Imagery and Geographic Information System (GIS) analysis. Firstly, observations on ESRI Land Cover which displays a global map of land use or land cover (LULC) derived from ESA Sentinel-2 Imagery at a resolution of 10 m. The results showed that the area of forest cover has decreased and the built-up area has increased in the 2017-2018 and 2021-2022. Secondly, using the EO Browser, namely Sentinel-2, that was done in one to search for and compare images using high resolution at these sources, there were 19 land cover changes, such as increasing residential land use, while forest land allotment decreased.